Kebersihan Alam Sekitar Mengikut Perspektif Islam - Abd. Rahman, Mohd. Muhiden (Jurnal Usuluddin, 1997)
Clealiness is an essential of life which not only prevents diseases but also symbolises the digree of the development of a nation. Islam places a special emphasis on clealiness and makes it a part of its teaching.The article elaborates the concept and goes beyond individual clealiness to regard it as a factor in environmental wellbeing.